Microwave-assisted extraction for methylmercury determination in sediments by high performance liquid chromatography-cold vapour-atomic fluorescence spectrometry - Ramalhosa, Elsa (2001)
A simple and rapid procedure for methylmercury extraction from sediments based on microwave-assisted alkaline digestion with methanolic potassium hydroxide was optimized on parameters such as microwave power, extraction time and sample size. Organomercury species were extracted with dichloromethane in hydrochloric acid medium and back-extracted into ultra-pure water. The sediment extracts were injected into an analytical system composed of high-performance liquid chromatography-ultraviolet-post-column oxidation-cold vapour-atomic fluorescence spectrometry (HPLC-UV-PCO-CV-AFS) for methylmercury determination. Quantitative methylmercury recoveries were obtained when 0.15 g of sediment were suspended into 6 mi of 25% m/v methanolic potassium hydroxide and the slurry was exposed to microwave irradiation at 84 W for 2 min. The detection limit of proposed method was 12 ng g(-1) while the relative standard deviation was less than 5%. The method was validated by the analysis of two sediment certified reference materials and the methylmercury concentrations found were in good agreement (95% confidence level) with the certified values.